Tax Illiteracy among Taxpayers in Malaysia - Vellanthurai, Shanmughanathan (1998)
The extent of taxpayer knowledge can have a major impact on the degree of compliance with taxation rules and regulation. Most importantly, uncertainty about the requirements of the tax regulation can lead to a high degree of involuntary non-compliant simply "get it wrong" without any intention to evade tax. The main problem is ambiguity and complexity in tax regulation, which can make it difficult for even the most conscientious of taxpayers to fully satisfy their legal obligations unless they take authority employees, private consultant, academician and etc. Information on the extent of taxpayers knowledge is potentially useful to the tax authorities in so far as it can assist in the development of effective compliance enhancement policies. For example, if knowledge of a particular area of the tax regulation is low, compliance is also likely to be low on the relevant items. Followup research can determine the extent of the problem and appropriate action ranging from clarification or interpretation of the regulation to complete re-writing of the relevant section can be undertaken. In addition if investigations reveal that particular subsets of taxpayers have low levels of knowledge, in general or in relation to particular aspects of the tax regulation, compliance-enforcement campaigns may be targeted more effectively. Surveys to assets the extent of taxpayers knowledge about tax regulation have been carried out in Klang Valley. This paper reports on the findings of the survey. The survey revealed a generally reasonable level of understanding of many aspects of the tax regulation, though with a wide variation between different groups in the population. The survey procedure and sample covered by the survey are outlined in these papers, together with a summary of the survey results.